PENGARUH EMPLOYEE ENGAGEMENT TERHADAP WORK-LIFE BALANCE KARYAWAN - Ariawaty, R. Rina Novianty (BISMA: Jurnal Bisnis dan Manajemen, 2019)
A company’s objective to create employee engagement is to maintain the loyalty of its human resources. Employee engagement is directly related to the allocation of employee’s role and time inside and outside of their work environment as part of the work-life balance dimension. The purpose of this research is to analyze the effect of employee engagement on the employee’s work-life balance in the Bank X. The sample consisted of 39 employees collected by applying census sampling. Data were analyzed using PLS. The results indicated that employee engagement had a significant effect on employee work-life balance in the Bank X. This finding implies that employee’s work-life balance could be weakened or strengthen depends on the level of their engagement towards the company or organization. Keywords: employee engagement, work-life balance